Drug Courts and the Facilitation of Turning Points: An Expansion of Life Course Theory. (March 2016) - Messer, Sarah; Patten, Ryan; Candela, Kimberlee
Life course theory has been used to explain why people stop committing crime and/or deviant behavior. Life course theory scholars have demonstrated important life events, such as marriage, gaining employment, or joining the military, have led to reduced recidivism; however, drug courts might also legitimately be considered a turning point for an offender. This study utilized semi-structured interviews with former drug court participants ( n = 29) in an attempt to expand life course theory and demonstrate how drug courts should be considered a facilitator of "turning points" for previous criminal offenders. During the interviews, participants discussed how drug court helped them attain many important skills/ideas: self-esteem, improved relationships with family and children, a general educational development certificate, a driver's license, and/or gainful employment. A gendered analysis demonstrates women found drug court to be more useful at facilitating turning points than their male peers. Additionally, recidivism rates for the participants were lower than similarly situated offenders at the state level. While further research is needed, this study begins to advance the expansion of life course theory.